Advance in Composite Gels - Takeno, Hiroyuki (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the last few decades, various composite gels have been developed. In recent years, further advances have been made in the development of novel composite gels with potential applications in various fields. This reprint offers the latest findings of composite gels by experts throughout the world.